ANALISIS PENGARUH FAKTOR KEPUTUSAN PEMBELIAN DENGAN STRUCTURAL EQUATION MODELING PARTIAL LEAST SQUARE - Sukimin, Sukimin; Fidriani, Eva; Miswaty, Miswaty; Juwari, Juwari (MEDIA RISET EKONOMI [MR.EKO], 2022)
The purpose of this paper is to idendify the factors affecting consumersâ€™ purchase decision making at Angkringan Â in Balikpapan. Data were collected by distributing questionnaires to 177Balikpapan consumes who were actively buying Â food of angkringan. The data were analyzed using Â the partial least squares structural equation model (PLS-SEM) and multi group analysis (MGA) in SMARTPLS software.. The results show that the product and location have an impact on purchasing decisions. This study illustrates that the determination of product and location are important factors that need to be considered to increase sales due to increased purchasing decisions by consumers. The purchase decision considers the convenience and location that is suitable for buyers to come to the place of business, ease of access and becomes a determinant for buyers and influences buyers’ decisions. Suggestions from this study that paying attention to location and product quality will increase purchases.